Analisis Potensi Pembentukan Bank Sampah Sebagai Upaya Pembangunan Berkelanjutan (Studi Kasus: Dusun Celungan, Desa Sapen, Kecamatan Mojolaban, Kabupaten Sukoharjo) - Yogi Pasca Pratama; Bhimo Rizky Samudro; Sutomo Sutomo (Trunojoyo University of Madura, 2019)
This study aims to describe the waste management system in Celungan, Sapen Village, Sukoharjo then compare with the pattern that occurs in established waste banks. The results of the comparison are used to analyze the potential development of existing waste management systems to be developed into a waste bank system. The results of the study show the general pattern needed to establish a waste bank, namely the awareness and participation of the community, as well as the clarity of the management structure and the system of the waste bank being run. What happened at the research site was community awareness about waste management, but it was not balanced with the support of a good management system. So that development efforts are needed in the form of training, preparation of management structures, preparation of waste bank systems, and support for necessary facilities.Keywords: Waste Bank, Community Economics, Waste Management